Bibliometric Analysis and Challenges in Biofuel Production using Petroplants - Cherian Pinkie; Jayakumar Devika; PA Majidha (Revue des Énergies Renouvelables, 2022)
A bibliometric analysis based on PubMed database were carried out to provide insights into research activities and tendencies, challenges of global biodiesel from 1997-2020.The document type and language,characteristics of publication output, keywords and most cited articles were emphasized. The biofuel production faces many challenges which include land availability, high cost, plant health and availability of labour. Data visualization using VOS viewer clearly stated that annual output of related scientific articles increased steadily. On analyzing the keywords, network visualization showed 100 lines with biofuel most related to biotechnology field.The most ideal keyword occurrence were visualized for bio-oil followed by co- digestion of biological matter are seen for density visualization. Six clustering of keywords were noted with links 20,6701 among keywords. The relevance score calculated using VOS viewer software generated 2.35 as score for Biodiesel engine and 2.25 for Organic loading rate. The analysis of review papers from pubMed clearly indicated that biofuels showed direct link to biotechnology field, plant oils and ethanol production.